Keimanan Abraham Berdasarkan Ibrani 11 - Sinambela, Juita Lusiana; Sinaga, Janes; Tinenti, Max Lucky; Pelawi, Stepanus (SOPHIA: Jurnal Teologi dan Pendidikan Kristen, 2022)
Abstract: The story of the Bible character Abraham is a source of inspiration for every human being living in this world to continue to believe in God. Abraham is listed in Hebrews chapter 11 as a believer or believer. Abraham was an ordinary man and sometimes lived in weakness and doubt in his actions, but his act or obedience to God by accepting his call out of his hometown to a foreign land for him as a promised land for him. Abraham was also called a believer when he obeyed God's command to sacrifice his son Isaac on Mount Moriah as a burnt offering, which was offered to God, although in the end God offered a substitute sacrifice. The story of Abraham states that everyone has the opportunity to be called a believer like Abraham by obeying and believing in God's commands. This research was conducted using a qualitative method by collecting literature data from a bibliography such as the Bible, books and journals, so that it can lead everyone to become a believer like Abraham Abstrak: Kisah tokoh Alkitab Abraham menjadi sumber inspirasi bagi setiap manusia yang hidup di dunia ini untuk tetap percaya kepada Tuhan. Abraham dicatatkan dalam kitab Ibrani pasal 11 sebagai orang percaya atau beriman. Abraham adalah manusia biasa dan kadang kala hidup dalam kelemahan dan keraguan dalam tindakannya, namun tindakan atau penurutannya kepada Allah dengan menyambut panggilannya keluar dari kampung halamannya ke negeri asing baginya sebagai tanah perjanjian baginya. Abraham juga disebut beriman ketika dia menuruti perintah Allah untuk mengorbankan Anaknya Ishak di bukit Moria sebagai korban bakaran, yang dipersembahkan kepada Tuhan, walaupun pada akhirnya Allah memberikan korban pengganti. Kisah Abraham menyatakan kepada setiap orang memiliki kesempatan disebut menjadi orang percaya seperti Abraham dengan menurut dan percaya kepada akan perintah Tuhan. Penelitian ini dilakukan dengan menggunakan metode kualitatif dengan mengumpulkan data-data literatur dari daftar Pustaka seperti Alkitab, buku-buku dan jurnal, sehingga dapat menuntun setiap orang untuk menjadi orang beriman sebagaimana halnya Abraham.